Immediate and delayed effects of eccentric exercise on proprioception of the knee - Laursen, Jens (2009)
The study investigated the effects of eccentric exercise of the quadriceps on proprioception of the knee in open- and closed-chain tasks. Fifteen healthy adults (9 men; age 25.0 ± 3.6 yrs) participated. Proprioception of the right leg was assessed at 120º and 150º of knee extension before, immediately post, and 24h following eccentric exercise of the quadriceps with 3 tests: 1. matching the position of the right knee to the left knee; 2. repositioning of the right knee after active movement (open chain); 3. repositioning after active movement in standing. Immediately after the exercise and 24h post exercise, maximum knee extension force was reduced with respect to baseline (percent reduction, 77.0 ± 12.3 % and 82.7 ± 16.2%, respectively; P<0.001). For the position matching task at 120°, proprioceptive acuity of the right knee was reduced immediately following eccentric exercise (error, 12.3 ± 5.6˚) compared to baseline (5.8 ± 2.7˚) (P<0.001). 24h post exercise, the positioning error (8.1 ± 4.5˚) was lower than immediately after the exercise (P<0.05) but greater than in the baseline condition (P<0.05). Proprioception of knee extension was also impaired during the open-chain repositioning task, both immediately (error 120°, 5.9 ± 3.1˚, P<0.05) and 24h post exercise (5.2 ± 2.9˚, P<0.05). Conversely, the repositioning task in weight bearing was performed with similar error as in the baseline condition. In conclusion, eccentric exercise of the quadriceps impairs proprioception of the knee both immediately after and 24h after exercise, however this effect was not observed in the weight bearing task.